Language nutrition for language health in children with disorders: a scoping review - Bang, Janet Y; Adiao, Aubrey S; Marchman, Virginia A; Feldman, Heidi M (Pediatric research, 2020)
The quantity and quality of child-directed speech-language nutrition-provided to typically-developing children is associated with language outcomes-language health. Limited information is available about child-directed speech to children at biological risk of language impairments. We conducted a scoping review on caregiver child-directed speech for children with three clinical conditions associated with language impairments-preterm birth, intellectual disability, and autism-addressing three questions: (1) How does child-directed speech to these children differ from speech to typically-developing children? (2) What are the associations between child-directed speech and child language outcomes? (3) How convincing are intervention studies that aim to improve child-directed speech and thereby facilitate children's language development? We identified 635 potential studies and reviewed 57 meeting study criteria. Child-directed speech to children with all conditions was comparable to speech to language-matched children; caregivers were more directive toward children with disorders. Most associations between child-directed speech and outcomes were positive. However, several interventions had minimal effects on child language. Trials with large samples, intensive interventions, and multiple data sources are needed to evaluate child-directed speech as a means to prevent language impairment. Clinicians should counsel caregivers to use high quality child-directed speech and responsive communication styles with children with these conditions.